Delayed ionospheric response to solar extreme ultraviolet radiation variations: A modeling approach. Issue 6 (15th March 2022) - Vaishnav, Rajesh; Jacobi, Christoph; Berdermann, Jens; Schmölter, Erik; Codrescu, Mihail
Abstract: The behavior of the ionosphere is strongly dependent on solar activity conditions. Attempts have been made to understand the delayed response of the ionosphere at low and high solar activity in a systematic way. The total electron content provided by International GNSS Service (IGS) and Coupled Thermosphere Ionosphere Plasmasphere electrodynamics (CTIPe) was used to study the delay during 2008 and 2013 at the location 50 ° N, 18 ° E. The comparative study shows that the model successfully reproduces the ionospheric behavior during low and high solar activity. In addition, the CTIPe has been used for sensitivity studies with different model components. The analysis suggests that the model reproduction of the ionospheric time delay is significantly affected by various processes such as diffusion, photodissociation, solar and geomagnetic activities. To this end, several model runs were performed during low and high solar activity conditions. Furthermore, we have systematically studied the delayed response of the ionosphere during low, medium, and high solar activity and it was confirmed that the ionospheric delay increases with increasing solar activity.